A Genetic Screen Identifies a Critical Role for the WDR81‐WDR91 Complex in the Trafficking and Degradation of Tetherin. (25th May 2016) - Rapiteanu, Radu; Davis, Luther J.; Williamson, James C.; Timms, Richard T.; Paul Luzio, J.; Lehner, Paul J.
Abstract : A genetic screen in human haploid cells identifies a critical role for the WDR81‐WDR91 complex in the degradation of tetherin – a potent viral restriction factor. Subsequent experiments show that this complex plays a general role in the degradation of internalized plasma membrane proteins as it is also required for EGFR degradation. Depletion of WDR81 leads to the appearance of markedly enlarged early and late endocytic vesicles and to impaired delivery of cargo to lysosomes. Abstract : Tetherin (BST2/CD317) is a viral restriction factor that anchors enveloped viruses to host cells and limits viral spread. The HIV‐1 Vpu accessory protein counteracts tetherin by decreasing its cell surface expression and targeting it for ubiquitin‐dependent endolysosomal degradation. Although the Vpu‐mediated downregulation of tetherin has been extensively studied, the molecular details are not completely elucidated. We therefore used a forward genetic screen in human haploid KBM7 cells to identify novel genes required for tetherin trafficking. Our screen identified WDR81 as a novel gene required for tetherin trafficking and degradation in both the presence and absence of Vpu. WDR81 is a BEACH‐domain containing protein that is also required for the degradation of EGF‐stimulated epidermal growth factor receptor (EGFR) and functions in a complex with the WDR91 protein. In the absence of WDR81 the endolysosomal compartment appears swollen, with enlarged early and late endosomes and reduced delivery of endocytosed dextran to cathepsin‐active lysosomes. Our data suggest a role for the WDR81‐WDR91 complex in the fusion of endolysosomal compartments and the absence of WDR81 leads to impaired receptor trafficking and degradation.